The Centrality of Reflexivity Through Narrative Beginnings: Towards Living Reconciliation. (July 2018) - Dubnewick, Michael; Clandinin, D. Jean; Lessard, Sean; McHugh, Tara-Leigh
Autobiographical narrative inquiry is an approach with a specific set of methodological commitments that guide research practice, yet its place and position within the work on reflexive practice are lost or misrepresented. Reflexivity in the form of autobiographical narrative inquiries comes out of the relational ontological commitments of narrative inquiry. By inquiring into Michael's (the first author) experience as a researcher–practitioner, the purpose of this article is to show how reflexivity, in the form of narrative beginnings, is situated in the ongoing stream of experience. It provides narrative inquirers with avenues to make clear their research justifications/puzzles, become wakeful and open in their inquiries, and support shifts in relational knowing and being. By looking back and noticing the ways stories work on us, rather than us on them, this research explores the reverberations of past experiences and the ripples that carry forward into our future inquiries.